El derecho de la OIT en las demandas individuales presentadas ante el Tribunal Europeo de Derechos Humanos - Sanz Rubiales, Susana (Revista de Derecho, 2019)
This article shows the most social side of the European Court of Human Rightsthrough the location and legal analysis of those judgments in which either the partiesor the Court itself, have invoked the work and standards of the International LabourOrganization. This aspect of the Strasbourg Court case law is poorly understoodbecause the rights that the European Convention on Human Rights includes are ofa civil and political character. However, the Court has used several techniques inorder to protect economic and social rights. The use of these techniques has allowedthe development of a social case law which is primarily based on five provisions ofthe Convention: the prohibition of forced labour, the right to respect for private and family life, the freedom of expression, the freedom of assembly and association andthe prohibition of discrimination. In a number of these judgments the Court has usedthe ilo Law as a reference and guide due to the organization’s specialization in theprotection of labour rights.
Keywords: ilo and ECtHR; European case law on the ilo Law; ocial case law of the ECtHR